Ideas mapping , surface computing and user experience - Zaphiris, Panayiotis; Ioannou, Andri; Loizides, Fernando; Vasiliou, Christina (My University, 2012)
This paper reports work regarding the design, development and evaluation of a surface computing application to support collaborative decision making.. The domainindependent application, so called Ideas Mapping, builds on the principle of Affinity Diagramming to allow participants to analyze a problem and brainstorm around possible solutions while they actively construct a consensus artifact - - a taxonomy of their ideas. During idea generation, Ideas Mapping replicates physical post-it notes on a multi-touch tabletop. Additional functionality supports student collaboration and interaction around the organization of ideas into thematic categories associated with the problem at hand. We report on the functionality and user experience while interacting with the application which was designed and developed using a user-centered approach. We also report initial findings regarding the affordances of surface computing for collaborative decision making.
Keywords: Surface computing; User experience; Collaborative decision making; CSCL